Respuesta :
n= -20/133
Step 1: Simplify both sides of the equation.
−
2
(
−
4
n
+
1
)
+
5
(
25
n
−
8
)
=
−
62
(
−
2
)
(
−
4
n
)
+
(
−
2
)
(
1
)
+
(
5
)
(
25
n
)
+
(
5
)
(
−
8
)
=
−
62
(Distribute)
8
n
+
−
2
+
125
n
+
−
40
=
−
62
(
8
n
+
125
n
)
+
(
−
2
+
−
40
)
=
−
62
(Combine Like Terms)
133
n
+
−
42
=
−
62
133
n
−
42
=
−
62
Step 2: Add 42 to both sides.
133
n
−
42
+
42
=
−
62
+
42
133
n
=
−
20
Step 3: Divide both sides by 133.
133
n
133
=
−
20
133
n
=
−
20
133
Step 1: Simplify both sides of the equation.
−
2
(
−
4
n
+
1
)
+
5
(
25
n
−
8
)
=
−
62
(
−
2
)
(
−
4
n
)
+
(
−
2
)
(
1
)
+
(
5
)
(
25
n
)
+
(
5
)
(
−
8
)
=
−
62
(Distribute)
8
n
+
−
2
+
125
n
+
−
40
=
−
62
(
8
n
+
125
n
)
+
(
−
2
+
−
40
)
=
−
62
(Combine Like Terms)
133
n
+
−
42
=
−
62
133
n
−
42
=
−
62
Step 2: Add 42 to both sides.
133
n
−
42
+
42
=
−
62
+
42
133
n
=
−
20
Step 3: Divide both sides by 133.
133
n
133
=
−
20
133
n
=
−
20
133
Answer:
n = 0.15037593985
Step-by-step explanation:
−2(−4n + 1)+5(25n − 8)=−62
8n-2+125n-40= -62
133n = -20
133/133 = 20/133
n = 0.15037593985
This equation might be screwed up; I'd talk to your teacher about it.